Phosphohistone H3 labelling for histoprognostic grading of breast adenocarcinomas and computer-assisted determination of mitotic index. Issue 7 (3rd February 2006) - Bossard, C; Jarry, A; Colombeix, C; Bach-Ngohou, K; Moreau, A; Loussouarn, D; Mosnier, J-F; Laboisse, C L
Abstract : Background: Microscopic evaluation of mitotic figures is a routine procedure in the assessment of the histoprognostic grade of tumours. Nevertheless, their count may be fraught with difficulties. As histone H3 phosphorylation at serine 10 is closely linked to chromosomal condensation, a new monoclonal antibody directed to phosphorylated histone H3 (PPH3) was recently proposed to detect mitotic cells. Aim: To test the reliability of this antibody in detecting and counting mitotic figures in sections of breast adenocarcinomas, because of the importance of mitotic count in histoprognostic grading. Methods: The pattern of PPH3 staining in formalin-fixed paraffin wax-embedded tissues, including normal tissues and a series of 39 breast adenocarcinomas, was examined. A new computer-assisted method was also developed for determining the mitotic index. Results and conclusions: In all tissues tested, PPH3-labelled mitotic figures were easily detected, allowing a rapid identification of the area of highest mitotic activity. In breast carcinomas, a strong correlation was observed between PPH3-stained and haematoxylin and eosin-stained mitotic counts (r = 0.86, p<0.0001). Counting of prophase nuclei that coexpress cyclin B1, a marker of the G2/M phase, was possible by PPH3 staining; its accuracy led us to reconsider the tumour grade in three cases. Finally, an automatic computer-assisted method was designed for assessing mitotic index with confocal microscopy and image-analysis software.